Influence of Seasonality on the Diversity, Abundance, and Distribution of Hornbill Species in Bali and Gassol Local Government Areas, Taraba State, Nigeria - Cletus Tari; Delphine Leila David; Awai Peter Andrew; Julius Yani J; Tari Rubang Samuel (Darul Yasin Al Sys, 2025)
This study investigates the seasonal dynamics of hornbill diversity, abundance, and distribution in Bali and Gassol Local Government Areas of the central zone of Taraba State, Nigeria, a biodiverse region currently experiencing hornbill population decline. The objectives were to assess species composition, seasonal abundance, and habitat-specific distribution of hornbills across wet and dry seasons. A multistage stratified sampling method was applied, categorizing the study area into woodland savannah and open grassland as sampling sites. Hornbill surveys were conducted using the point count method. A total of 1,216 individuals representing three species—the African Grey Hornbill, African Pied Hornbill, and Red-billed Hornbill—were recorded, with higher diversity and abundance observed in the wet season due to increased food and water availability. Woodland savannah supported larger populations (753) compared to open grassland (463), attributed to its complex vegetation, nesting opportunities, and favorable microclimates. The African Grey Hornbill dominated across habitats and seasons (50–70%). Human activities, particularly bushfires, exacerbated dry season declines in open grasslands. Despite seasonal fluctuations in abundance, species richness remained stable across both habitats. Distribution patterns showed significant deviations from expected uniformity, indicating species-specific habitat and seasonal preferences. The study concludes that hornbill conservation in Central Taraba requires recognition of habitat preferences and seasonal ecological dynamics. It recommends community-based initiatives to raise conservation awareness, promote sustainable land use, and encourage practices that support hornbill population recovery and long-term biodiversity conservation.